Profits and markups during the post-COVID-19 inflation shock in the U.S. economy: a firm-level lens - Leila Davis (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
In this paper, I use firm-level data from Compustat to document the evolution of markups among listed U.S. non-financial firms during the height of the COVID-19 pandemic (2020-2022). I show that, continuing its long-term rise, the aggregate (sales-weighted) markup rises markedly in 2020 and moderately in 2021, and returns to pre-pandemic levels in 2022. I then disaggregate this aggregate trend to, first, show that its 2020 growth reflects growing sales concentration. In contrast, the average within-firm markup is steadier than the aggregate. Second, I show that the markup distribution widens during the pandemic, due largely to increases at its 90th percentile. At the same time, however, the cross-sectional distribution obfuscates that firms with low pre-pandemic markups command notable markup growth in both 2021 and 2022. Third, I document key roles for manufacturing, retail, and information services in these dynamics. Together, these patterns are consistent with accounts of profit inflation, wherein U.S. firms' market power allowed them to maintain - and, for some firms, increase - their margins over direct costs in the face of input cost shocks in 2020-2022.
Keywords: E12; E25; E31; E61; 330; Market power; Markups; Profit inflation